Who Is Responsible for Killer Robots? Autonomous Weapons, Group Agency, and the Military‐Industrial Complex. - Taylor, Isaac (Journal of Applied Philosophy, 2021)
There has recently been increasing interest in the possibility and ethics of lethal autonomous weapons systems (LAWS), which would combine sophisticated AI with machinery capable of deadly force. One objection to LAWS is that their use will create a troubling responsibility gap, where no human agent can properly be held accountable for the outcomes that they create. While some authors have attempted to show that individual agents can, in fact, be responsible for the behaviour of LAWS in various circumstances, this will not be possible in all cases. This article argues, however, that by assigning responsibilities to group agents operating within the military‐industrial complex, as well as the military‐industrial complex as a whole, we may be able to close the responsibility gap, or at least reduce its costs. Insofar as the potential for responsibility gaps poses an ethical barrier to the development and deployment of LAWS, this argument, if sound, may show their use to be morally permissible in a greater range of cases.